Pemanfaatan Aplikasi Mitigasi Bencana Berbasis Android dalam Pembelajaran IPS - Slamet Slamet; Suwarno Suwarno (UM Purwokerto Press, 2022)
Geological location of Indonesia is at the confluence of active plates and 2 active mountain lines and is in a tropical climate, so most of Indonesia is prone to natural disasters. There are various kinds of natural disasters in Indonesia so that Indonesia is known as a Natural Disaster Laboratory. The Indonesian people, especially the young generation of the nation's heirs, really need to get disaster mitigation education as an effort to create a disaster-resilient generation. Disaster mitigation education for millennial generation students must be adjusted, according to Ki Hajar Dewantara's message